PORTFOLIO ASSESSMENT OF TPACK APPROACH-BASED MATHEMATICS SUBJECTS IN PRIMARY SCHOOLS - Sri Gianti; Rochmiyati Rochmiyati; Nurhanurawati Nurhanurawati (Teunuleh Publisher, 2021)
Assessing students' knowledge and success during and after learning and teaching is an ingrained part of education because it offers the most important specifics for teachers. This action research aims to determine the influence of portfolio assessment in TPACK-based mathematics subjects. The two methods used include student portfolio attitude surveys and teacher surveys. It found that most students had a clear understanding of how portfolios were created and recognized that portfolios could help them in learning maths better in many aspects. Likewise, most teachers consider portfolios practical especially in pointing out student problems and monitoring their learning progress.